Implementasi Penyiraman Tanaman Otomatis dengan Kontrol Jarak Jauh Menggunakan Aplikasi Blynk - Taufiqurrahman, Taufiqurrahman; Diantoro, Karno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Effective and efficient plant watering remains a major challenge in the agricultural sector, especially for farmers with limited time and resources. This study aims to develop an automatic plant watering system based on the Internet of Things (IoT), which can be remotely controlled using the Blynk application. The system utilizes an ESP32 microcontroller as the central controller, a soil moisture sensor to indicate water requirements, and an RTC DS3231 module to ensure scheduled watering continues even if the internet connection is interrupted. The research methodology follows the System Development Life Cycle (SDLC) with the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance. Test results show that the system is capable of detecting soil moisture in real-time and controlling the water pump based on detected conditions. The Blynk application allows users to monitor soil status and manage watering manually or automatically. When the internet connection is lost, the RTC DS3231 module continues to execute the scheduled watering as configured. The implementation of this system improves water usage efficiency by up to 30% compared to manual methods while providing flexibility and ease in plant management. This research contributes to the application of IoT technology in agriculture, supports more sustainable resource management, and introduces a smart irrigation system that adapts to network conditions and plant needs.